AN ARCHAEOLOGICAL STUDY OF THE WESTERN URALS AT THE BEGINNING OF XXI CENTURY: EXPEDITIONARY, RESEARCH AND PUBLISHING PROJECTS - Belavin, A.M. (Perm Federal Research Centre Journal, 2016)
A study of the history of the Western Urals and adjacent territories is investigated by archaeologists and historians of the Department of History, Archaeology and Ethnography of the Perm Scientific Centre in the modern period. The directions and theme of the carried out research and their results are analyzed, some promising areas of scientific research are defined.